Preparation and characterization of an iron oxide-hydroxyapatite nanocomposite for potential bone cancer therapy - Sneha M (Dove Medical Press, 2015)
Murugesan Sneha, Nachiappan Meenakshi Sundaram Department of Biomedical Engineering, PSG College of Technology, Tamil Nadu, India Abstract: Recently, multifunctional magnetic nanostructures have been found to have potential applications in biomedical and tissue engineering. Iron oxide nanoparticles are biocompatible and have distinctive magnetic properties that allow their use in vivo for drug delivery and hyperthermia, and as T2 contrast agents for magnetic resonance imaging. Hydroxyapatite is used frequently due to its well-known biocompatibility, bioactivity, and lack of toxicity, so a combination of iron oxide and hydroxyapatite materials could be useful because hydroxyapatite has better bone-bonding ability. In this study, we prepared nanocomposites of iron oxide and hydroxyapatite and analyzed their physicochemical properties. The results suggest that these composites have superparamagnetic as well as biocompatible properties. This type of material architecture would be well suited for bone cancer therapy and other biomedical applications. Keywords: iron oxide, hydroxyapatite, nanocomposite, superparamagnetic, bone cancer